From the Pulpit to the Screen: The Dynamics of Fatwa Mediatization on Philanthropy in Indonesia - Hidayat, Mansur; Ichwan, Moch. Nur (FIKRAH, 2025)
This article analyzes the dynamics of the mediatization of religious fatwas concerning alms (philanthropy) in Indonesia, identifying patterns and changes in the delivery and acceptance of fatwas since the post-Soeharto reform era. The main focus of this article is how media not only serve as channels of information but also act as agents shaping religious narratives. The process of mediatization shows a significant shift in how fatwas are received and practiced by the people. This shift reflects changes in public perceptions of the obligation to give alms and the responses of the ulama. Using a qualitative approach and discourse analysis techniques, this study distinguishes three emerging discursive positions: full acceptance of fatwas through media, adaptation of fatwas to modern media contexts, and rejection of the mediatization of fatwas. The article concludes that the mediatization of fatwas concerning alms highlights the inability of traditional views to persist without adaptation in the context of modern media in present-day Indonesia.